Portugal : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This Selected Issues paper and Statistical Appendix on Portugal attempts to 'feel the pulse' of Portugal's banking system on the eve of European Monetary Union. It surveys the reforms of the financial sector, explores whether prudential concerns have arisen in the process of liberalization, and gauges how well prepared the Portuguese banking system is for heightened competition from abroad. The paper also draws policy lessons from its approach to reform. The paper reviews the financial liberalization process prior to Portugal's accession to the European Union and its broadening thereafter.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet